Across the city, toward the nation Philippine poetry, metropolitan trains, and the Tulaan sa Tren project - Serquina, Oscar Tantoco Jr. (2014)
In 2008 and 2010, the Philippine government’s National Book Development Board (NBDB) and Light Railway Transit Authority (LRTA) launched Tulaan sa Tren, a project “designed to provide train passengers with an appreciation for Philippine Literature as they listen to their favorite celebrities reading poems about Manila over the public announcement system of LRT Line 2 stations” (goodnewspilipinas.com). This project also initiated a poetry writing contest and produced poetry anthologies that predominantly depicted views of the city and city life. Part appreciation, part revaluation, part critique, this paper initiates a sensing of: (1) the train as a figure of modern life; (2) NBDB and LRTA’s enterprise as a state measure to bridge the disparity between the public’s reception to Philippine literature and the intelligentsia’s academic way of life; and (3) literary representations of the city in the poetry anthologies this project produced, namely Train of Thought: Poems from Tulaan sa Tren and Off the Beaten Track: Poems from Tulaan sa Tren 2. This paper argues that the institutional intervention of popularizing travel, literature, and the city may be seen as a way of generating a socio-political and literary consciousness among train commuters who are linked to and implicated in the issues and anxieties of their lives in the urban environment. By analyzing the poems in the anthologies, this essay ultimately critiques Tulaan sa Tren’s attempt at nation building, identity making, and city mapping.
Keywords: Art in public transit; Poetry -- Appreciation and Interpretations; Tulaan sa Tren Project